Peningkatan Minat Belajar Siswa Kelas VIII.B melalui Layanan Bimbingan Kelompok Masa Covid-19 SMPN 3 Masbagik - Nuraida, Nuraida (MASALIQ, 2021)
This counseling guidance class action research aims to determine the effectiveness of Classical Services in Increasing Student Interest in Class VIII.B SMPN 3 Masbagik Academic Year 2020/2021 during the covid-19 pandemic. By using classical guidance services, it focuses on providing maximum assistance so that the final hope can increase the level of student interest in learning in participating in learning activities in all subjects studied during the week. From this counseling guidance class action research, it was obtained that students' interest in learning in learning was obtained after guidance in the first cycle was obtained, the completeness level of learning interest was 69% and in the second cycle the student's interest in learning was 100%, meaning there was an increase from cycle I to cycle II. Thus, action research on counseling counseling classes by applying group guidance services can be said to be very effective in increasing student interest in learning in the learning process.